Advances and Insights of APC-Asef Inhibitors for Metastatic Colorectal Cancer Therapy - Yang, Xiuyan; Zhong, Jie; Zhang, Qiufen; Feng, Li; Zheng, Zhen; Zhang, Jian; Lu, Shaoyong (Frontiers in Molecular Biosciences, 2021)
In colorectal cancer, adenomatous polyposis coli (APC) directly interacts with the Rho guanine nucleotide exchange factor 4 (Asef) and releases its GEF activity. Activated Asef promotes the aberrant migration and invasion of colorectal cancer cell through a CDC42-mediated pathway. Knockdown of either APC or Asef significantly decreases the migration of colorectal cancer cells. Therefore, disrupting the APC - Asef interaction is a promising strategy for the treatment of invasive colorectal cancer. With the growth of structural information, APC-Asef inhibitors have been designed, providing hope for colorectal cancer therapy. Here, we will review the APC-Asef interaction in cancer biology, the structural complex of APC-Asef, two generations of peptide inhibitors of APC-Asef, and small molecule inhibitors of APC-Asef, focusing on research articles over the past 30 years. We posit that these advances in the discovery of APC-Asef inhibitors establish the protein-protein interaction (PPI) as targetable and provide a framework for other PPI programs.